Shrinking Rice Cultivation In Kerala - Shiji.O (Imperial Journal of Interdisciplinary Research (IJIR), 2016)
The agricultural sector is an important sub- sector of' the primary sector in Kerala. For the last several decades in Kerala the area under rice cultivation and rice production has shown more or less a consistent fall. Farmers divert their arable land for cash crops, despite rice being the staple food in the state and the state almost fully depends upon its import. The major factors that cause depletion of the rice cultivation are related with the socio cultural and economic changes in the state. The aim of this paper is to analyze the factors which are responsible for shrinking of rice field in Kerala. Basically this study is based on secondary data. So the main limitation of this study is that it does not depend on the primary data